2016
DOI: 10.5114/wiitm.2016.62800
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in open inguinal hernia repair: a literature review and summary of current knowledge.

Abstract: More than 1 million inguinal hernia repairs are performed in Europe and the US annually. Although antibiotic prophylaxis is not required in clean, elective procedures, the routine use of implants (90% of inguinal hernia repairs are performed with mesh) makes the topic controversial. The European Hernia Society does not recommend routine antibiotic prophylaxis for elective inguinal hernia repairs. However, the latest randomized controlled trial, published by Mazaki et al., indicates that the use of prophylaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
0
11
0
3
Order By: Relevance
“…while in developing countries, the incidence is reported to be nearly 8-10%. 4,5,[8][9][10] Current guidelines for perioperative prophylaxis are not clear on the routine use of antibiotics in children undergoing clean surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…while in developing countries, the incidence is reported to be nearly 8-10%. 4,5,[8][9][10] Current guidelines for perioperative prophylaxis are not clear on the routine use of antibiotics in children undergoing clean surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kekre et al reported a surgical site infection incidence of 0.41% [26]. Other studies have reported incidences as high as 8-10% in developing countries [27,28]. These differences in the incidence of surgical site infection following paediatric day case surgery are difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…Although several authors suggest that the number of the present bacteria, the bacterial virulence, and the wound microenvironment may have a critical role in the development of late-onset deep mesh infection there are not enough data to support this theory. It is more possible that these factors may play a more crucial role in the early infections than the late ones especially in those that develop several years after the operation [ 4 6 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lichtenstein technique is an open surgical technique for inguinal hernia repair based in the enhancement of the weakened inguinal floor by tension-free placing of a polypropylene mesh [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%